SEM-EDS to probing morphological and physiological changes produced by a porphyrin photosensitizer in psammobatis extenta electrocytes - Prado, María (2005)
The morphological and physiological changes produced by the intracellular localization of an alkyl long-chain tetraphenylporphyrin photosensitizer in Psammobatis extenta electrocytes were studied by means of SEM – EDS technique. The photosensitizer localize in the electromotor nerves and the nuclear chromatin of electrocytes. Both structures exhibited intense fluorescence, whereas, the mitochondria were only slightly fluorescent. Immediately after the penetration of the photosensitizer, the electrocytes swell and the convex faces lose all their invaginations. This effect is due to the flux of chloride and sodium ions into the electrocytes, in accord to the electron-probe X-ray microanalysis.